The role of climate on floristic composition in a latitudinal gradient in the Brazilian atlantic forest - Prata, Eduardo Magalhães Borges; Pádua Teixeira, Aloysio de; Joly, Carlos Alfredo; Assis, Marco Antonio (Plant Ecology and Evolution, 2018)
Background and aims – Latitudinal gradients have an important influence on species distribution reflecting the effects of environmental factors such as temperature, rainfall, soil, and geographical distance. In the southeastern Brazilian Atlantic Forest, the role of climatic variables in the floristic composition is better known for altitudinal gradients of the Serra do Mar Mountains rather than for the latitudinal gradient. Here, we investigated the effects of mean annual temperature and rainfall on tree species distribution and composition in a latitudinal gradient in the Atlantic forest. Methods – We calculated each species frequency of occurrence and the latitudinal range. We used multivariate analyses (direct ordination, Hierarchical Clustering followed by Indicator Species analysis and NMDS) to investigate variation in floristic composition, and regression analyses to evaluate mean annual temperatures and rainfall effects on tree species composition along the latitudinal gradient (21°S to 28°S). Key results – A total of 789 species were registered, of which a majority (646 species) were present in less than 20% of the sampled areas, and only four species (0.5%) were present in more than 80% of the sampled areas. Only ten species (1.3%) reached the maximum latitudinal range (~6°). We found a strong correlation between variation in floristic composition and the spatial position in the latitudinal gradient. The cluster analyses detected two main floristic groups, one composed by the forests from Rio de Janeiro (21°S to 23°S) and the second by the forests from São Paulo, Paraná and Santa Catarina States (23°S to 28°S). The multiple regression analysis revealed a strong effect of the climatic variables on the variation of the floristic composition along the latitudinal gradient (r 2 = 0.81, P < 0.001), where 62.82% of the variation were explained by mean annual temperature, 8.27% by annual rainfall and 10.45% by both variables together. Conclusions – The restricted distribution of most species may be explained by variations in mean annual temperature and annual rainfall along the latitudinal gradient. For instance, the decreasing mean annual temperature along the coast and the occurrence of frosts at higher latitudes may limit the southward distribution of some species while the lower annual rainfall (with marked seasonality) in the north of the gradient may limit the northward distribution of other species. Although mean annual temperature explained most of the variation in species composition along the latitudinal gradient, the abrupt variation in annual rainfall may explain the high floristic dissimilarity detected in the north of the gradient. © 2018 Meise Botanic Garden and Royal Botanical Society of Belgium. All rights reserved.